Islamic Wealth Management And Corporate Governance - Ihsan, Akmal; Nur, Abustan; Kadir, Syahruddin (El-Qish: Journal of Islamic Economics, 2022)
This paper aims to explore Islamic views on wealth (asset) management and look at good corporate governance. The research method used is a descriptive qualitative method with a literature review approach with data collection techniques namely literature study. The results of the study show that basically asset management in an Islamic perspective is wealth management which is seen as a process of ownership, consumption of wealth, and acquisition in accordance with sharia principles. Islam emphasizes the acquisition and utilization of assets in a lawful and best way. Wealth should not be left idle but must be productive, both in terms of obtaining assets and how to spend them, such as zakat, infaq, and alms. Corporate Governance in Islam is a process of managing assets in institutions or companies in accordance with Islamic principles. Where in the process must apply the principles that have been determined by the Shari'a, such as siddiq, amanah, tabligh, fathanah and so forth. So with the application of these principles, it is hoped that transparency, integration and accountability will be achieved in institutions or companies.